Anthocyanin accumulation in fruit crops: a multi-layered regulatory network integrating molecular, epigenetic, hormonal and environmental regulation - K. Anchana; S. Saraswathy; C. Rajamanickam; K. Venkatesan; M. Elayarajan; T. Anitha (Molecular Biology Reports, 2026)

High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

Novel biosynthesized zinc selenite photocatalysts for enhanced degradation of oxytetracycline and Rhodamine B dye with antibacterial activity - A. Anitha; P. Ponmurugan; D. Arunkumar; C. S. Sumathi; M. Sathishkumar; T. Purushothaman (BioMetals, 2025)

Recent Insights into the Neurobiology of Alzheimer’s Disease and Advanced Treatment Strategies - Anitha K; Mandeep Kumar Singh; Komal Kohat; Sri Varshini T; Santenna Chenchula; Padmavathi R; Lakshmi Sahitya Amerneni; Vishnu Vardhan K; Mythili Bai K; Madhav Rao Chavan; Shvetank Bhatt (Molecular Neurobiology, 2025)

Microproteins unveiling new dimensions in cancer - S. Daisy Precilla; Indrani Biswas; T. S. Anitha; B. Agieshkumar (Functional & Integrative Genomics, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Identification of sources of resistance and comparative metabolomic profiling of resistant and susceptible chilli germplasm to Meloidogyne incognita Race 1 - Prasanna Holajjer; T. P. Ahammed Shabeer; M. K. Mahatma; Z. Khan; S. R. Pandravada; N. Sivaraj; Anitha Kodaru; Anita Pardeshi (Australasian Plant Pathology, 2024)

Assessment of diversity in anti-nutrient profile, resistant starch, minerals and carbohydrate components in different ricebean (Vigna umbellata) accessions - Paras Sharma; Giridhar Goudar; Anil Kumar Chandragiri; R. Ananthan; K. Subhash; Anitha Chauhan; T. Longvah; Mohar Singh; Rakesh Bhardwaj; Swarup Kumar Parida; Amit Kumar Singh; Gayacharan; et al. (Food Chemistry, 2023)

Genetic mapping of drought tolerance traits phenotyped under varying drought stress environments in peanut (Arachis hypogaea L.) - Subhasini Ghosh; Supriya S. Mahadevaiah; S. Anjan Gowda; Sunil S. Gangurde; Mangesh P. Jadhav; Anil A. Hake; P. Latha; T. Anitha; V. P. Chimmad; Kiran K. Mirajkar; Vinay Sharma; Manish K. Pandey; et al. (Euphytica, 2022)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Statistical classification of streamflow based on flow variability in west flowing rivers of Kerala, India - T. K. Drissia; V. Jothiprakash; A. B. Anitha (Theoretical and Applied Climatology, 2019)

Experimental drought reduces genetic diversity in the grassland foundation species Bouteloua eriopoda - Kenneth D. Whitney; Joann Mudge; Donald O. Natvig; Anitha Sundararajan; William T. Pockman; Jennifer Bell; Scott L. Collins; Jennifer A. Rudgers (Oecologia, 2019)

Flood Frequency Analysis Using L Moments: a Comparison between At-Site and Regional Approach - T. K. Drissia; V. Jothiprakash; A. B. Anitha (Water Resources Management, 2019)

Genetic Diversity Among Indigenous Germplasm of Brassica juncea (L.) Czern and Coss, Using Agro-Morphological and Phenological Traits - Rashmi Yadav; Ranbir Singh; Sandeep Kumar; T. V. Prasad; Rakesh Bharadwaj; Vikender Kaur; Anitha Petapadi; Ashok Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Depth of soil compaction predominantly affects rice yield reduction by reproductive-stage drought at varietal screening sites in Bangladesh, India, and Nepal - Suresh Prasad Singh; Abhinav Jain; M. S. Anantha; Santosh Tripathi; Subarna Sharma; Santosh Kumar; Archana Prasad; Bhawana Sharma; Biswajit Karmakar; Rudra Bhattarai; Sankar Prasad Das; Shravan K. Singh; et al. (Plant and Soil, 2017)

De novo assembly and characterization of global transcriptome of coconut palm (Cocos nucifera L.) embryogenic calli using Illumina paired-end sequencing - M. K. Rajesh; T. P. Fayas; S. Naganeeswaran; K. E. Rachana; U. Bhavyashree; K. K. Sajini; Anitha Karun (Protoplasma, 2016)

Shallow geological environment of Krishna–Godavari offshore, eastern continental margin of India as inferred from the interpretation of high resolution sparker data - G ANITHA; M V RAMANA; T RAMPRASAD; P DEWANGAN; M ANURADHA (Journal of Earth System Science, 2014)

Scope of novel and rare bulbiferous coconut palms (Cocos nucifera L.) - B. A. Jerard; M. K. Rajesh; S. A. Elain; K. K. Sajini; Shafeeq Rahman; T. P. Fayas; Anitha Karun (Genetic Resources and Crop Evolution, 2014)

Effect of Aspect Ratio on the Monotonic Shear Behaviour: Micromechanical Interpretations - S. D. Anitha Kumari; T. G. Sitharam (Geotechnical and Geological Engineering, 2013)

Space-time structures of earthquakes - T. N. Krishnamurti; Ruby Krishnamurti; Anitha D. Sagadevan; Arindam Chakraborty; William K. Dewar; Carol Anne Clayson; James F. Tull (Meteorology and Atmospheric Physics, 2009)

Response surface methodology for optimization and characterization of limonene-based coenzyme Q10 self-nanoemulsified capsule dosage form - Anitha Palamakula; Mohammad T. H. Nutan; Mansoor A. Khan (AAPS PharmSciTech, 2004)

Lipoic acid attenuates hypertension and improves insulin sensitivity, kallikrein activity and nitrite levels in high fructose-fed rats - V. Thirunavukkarasu; A. T. Anitha Nandhini; C. V. Anuradha (Journal of Comparative Physiology B, 2004)

Estimation of reference values in liver function test in health plan individuals of an urban south Indian population - Sultana Furruqh; D. Anitha; T. Venkatesh (Indian Journal of Clinical Biochemistry, 2004)

The changing scenario in diagnosing prostate cancer - D. Anitha; T. Venkatesh (Indian Journal of Clinical Biochemistry, 2000)

Immunological characterization of spore proteins of the microsporidian Nosema bombycis - T. Anitha Sironmani (World Journal of Microbiology and Biotechnology, 1999)